Maternal alcohol use during pregnancy causes systemic oxidation of the glutathione redox system - Gauthier, Theresa W. (2009)
BACKGROUND: Increased systemic oxidant stress contributes to a variety of maternal complications of pregnancy. Although the antioxidant glutathione (GSH) and its oxidized component glutathione disulfide (GSSG) have been demonstrated to be significantly altered in the adult alcoholic, the effects of maternal alcohol use during pregnancy on oxidant stress in the post partum female remain under investigation. We hypothesized that maternal alcohol use would increase systemic oxidant stress in the pregnant female, evidenced by an oxidized systemic GSH redox potential. METHODS: As a subset analysis of a larger maternal language study, we evaluated the effects of alcohol consumption during pregnancy on the systemic GSH redox status of the post partum female. Using an extensive maternal questionnaire, post partum women where queried regarding their alcohol consumption during pregnancy. Any drinking, the occurrence of drinking > 3 drinks/occasion, and excessive drinking of >5 drinks/occasion during pregnancy were noted. Using HPLC, maternal plasma samples were analyzed for GSH, oxidized GSSH and the redox potential of the GSH/GSSG antioxidant pair calculated. RESULTS: Maternal alcohol use occurred in 25% (83/321) of our study sample. Two in ten women reported consuming > 3 drinks/occasion during pregnancy, while one in ten women reported consuming excessive alcohol at > 5 drinks/occasion. Any alcohol use during pregnancy significantly decreased plasma GSH (p<.05), while alcohol at >3 drinks/occasion or > 5 drinks/occasion significantly decreased plasma GSH concentration (p<0.05), increased the percent of oxidized GSSG (p<0.05), and substantially oxidized the plasma GSH redox potential (p<0.05). CONCLUSIONS: Alcohol use during pregnancy, particularly at levels of more than 3 drinks/occasion, caused significant oxidation of the systemic GSH system in the post partum women. The clinical ramifications of the observed alcohol-induced oxidation of the GSH redox system on high risk pregnancies or on the exposed offspring require more accurate identification and further investigation.